ANALISIS MEDIA SOSIAL DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI PADA SEPATU AEROSTREET - Amelia, Nabilah Indah; Ali, Hapzi; Khan, Muhammad Asif; Sawitri, Ni Nyoman; Navanti, Dovina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research is used to measure the effect of social media and product quality on purchasing decisions through purchase intention. This research is a quantitative study in which the objects used are students of Bhayangkara University, Greater Jakarta. This research was conducted using purposive sampling technique. The number of samples used in this study were 120 respondents. The data processing tool used is the structural equitation model (SEM) software application with the SmartPLS version 4.0 tool. based on the results of this study explain that; 1) Social media has a positive and significant effect on purchase intention; 2) Product quality has a positive and significant effect on buying interest; 3) social media has a positive and significant effect on purchasing decisions; 4) product quality has a positive and significant effect on purchasing decisions; 5) buying interest has a positive and significant effect on purchasing decisions.